2008
DOI: 10.1037/0012-1649.44.2.523
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind development in Chinese children: A meta-analysis of false-belief understanding across cultures and languages.

Abstract: Theory of mind is claimed to develop universally among humans across cultures with vastly different folk psychologies. However, in the attempt to test and confirm a claim of universality, individual studies have been limited by small sample sizes, sample specificities, and an overwhelming focus on Anglo- European children. The current meta-analysis of children's false-belief performance provides the most comprehensive examination to date of theory-of-mind development in a population of non-Western children spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
235
9
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(300 citation statements)
references
References 53 publications
(42 reference statements)
18
235
9
14
Order By: Relevance
“…False-belief understanding is the understanding that the human mind can have a false representation of the state of reality (Flavell, 2004). This representational understanding of the mind develops over the preschool years, with about 50% of 4-to 5-year-olds and nearly 100% of 8-to 9-year-olds passing standard false-belief tasks (Wellman, Cross, & Watson, 2001), a developmental pattern that has been replicated in Canada, India, Peru, Samoa, and Thailand (Callaghan et al, 2005) and in China (Lui, Wellman, Tardif, & Sabbagh, 2008;Sabbagh, Xu, Carlson, Moses, & Lee, 2006).…”
mentioning
confidence: 97%
“…False-belief understanding is the understanding that the human mind can have a false representation of the state of reality (Flavell, 2004). This representational understanding of the mind develops over the preschool years, with about 50% of 4-to 5-year-olds and nearly 100% of 8-to 9-year-olds passing standard false-belief tasks (Wellman, Cross, & Watson, 2001), a developmental pattern that has been replicated in Canada, India, Peru, Samoa, and Thailand (Callaghan et al, 2005) and in China (Lui, Wellman, Tardif, & Sabbagh, 2008;Sabbagh, Xu, Carlson, Moses, & Lee, 2006).…”
mentioning
confidence: 97%
“…Beginning around age 4 y, children answer correctly and point to the marble's original location; in contrast, younger children point to the marble's current location, as though they fail to understand that Sally holds a false belief about the marble's location. This developmental pattern (from below-chance to above-chance performance) has been observed in cultures around the world, although its timing varies somewhat across cultures (8,9). …”
mentioning
confidence: 99%
“…In fact, some studies have found partial support for this hypothesis (Hughes et al, 2014;Liu, Wellman, Tardif, & Sabbagh, 2008). For example, Liu et al (2008) compared Chinese children (i.e., from mainland China and Hong Kong) and North American children (i.e., children in the United States and Canada), and found that children from Canada develop theory of mind the earliest, those from the United States and mainland China came next, and those from Hong Kong were the last.…”
Section: Distal Environments and Theory Of Mindmentioning
confidence: 99%
“…For example, Liu et al (2008) compared Chinese children (i.e., from mainland China and Hong Kong) and North American children (i.e., children in the United States and Canada), and found that children from Canada develop theory of mind the earliest, those from the United States and mainland China came next, and those from Hong Kong were the last. Hughes et al (2014) compared Japanese, Italian, and British children, and reported that Japanese children developed theory of mind later than British children, again suggesting cultural influence on theory of mind.…”
Section: Distal Environments and Theory Of Mindmentioning
confidence: 99%